The Czech Republic in New Strategic Environment – Transforming the Role of the Armed Forces and Its Perception in Society (Czech Journal of International Relations, 1997)
Shortly after regaining sovereignty, Czechoslovakia at that time demonstrated its awareness of belonging to the international community by sending soldiers to the Persian Gulf and blue helmets to the area of ​​the former Yugoslavia. And the Czech Republic in this not long tradition of engagement continues. At the same time, it seems that the Czech public is accepting the new tasks of the armed forces for the time being with understanding and Ze does not reject the involvement of Czech soldiers in actions abroad. Furthermore, it can be assumed that the political-security situation after the end of the Cold War will increasingly require this kind of engagement.Participation in peacekeeping operations is just one of the challenges of the new situation after the end of the Cold War rolls. The transition from a closed company to an open one, which has been going on for us since 1989, will bring new risks and threats in addition to positive moments. The opening of the country and society and its gradual integration into European and Euro-Atlantic institutional structures make the Czech Republic more attractive and more accessible both for the establishment of various types of criminal activities (on a state and supranational scale), as well as for other non-state actors such as terrorist groups, fanatical sects, etc. point of view, one of the main general features of the new situation is a certain blurring of previously sharp boundaries between internal and external security. We believe that this trend requires, among other things, the transformation and distribution of the role of the armed forces.